The influence of religiosity and Islamic work environment on employee performance at the El-Nur El-Kasysyaf Islamic Boarding School (Yapink Pusat) in Bekasi - Ratu Nila Nahdilyah; Muhammad Agus Mushodiq; Finny Ligery (Revenue Journal: Management and Entrepreneurship, 2026)
The influence of religiosity and Islamic work environment on employee performance at the El-Nur El-Kasysyaf Islamic Boarding School (Yapink Pusat) in Bekasi